What Role Do Legal and Policy Frameworks Play in Integrating Local Heroes’ Wisdom into National Education? - Suryadi, Andy; Utomo, Cahyo Budi; Andriyanto; Purwono, Heni; Arifin, Ridwan (Jurnal Suara Hukum, 2026)
This study explores the role of legal and policy frameworks in integrating local heroes' wisdom into national education systems, particularly in the context of Indonesia’s efforts to reinforce national identity through local cultural values. In response to the challenges posed by globalization and transnational cultural flows, this paper advocates for a strategic approach that incorporates local heroes’ wisdom into educational curricula, with a particular focus on regions like Central Java, which are rich in historical narratives of local resistance. Despite the cultural and historical significance of local heroes, their wisdom remains fragmented and underutilized within the national education framework. This research examines the interplay between legal structures and educational policies in facilitating the inclusion of local wisdom in national curricula, highlighting relevant Indonesian laws such as Undang-Undang No. 20 Tahun 2003 tentang Sistem Pendidikan Nasional (National Education System Law), which emphasizes the need for education to reflect national culture, and Undang-Undang No. 5 Tahun 2017 tentang Pemajuan Kebudayaan (Cultural Advancement Law), which promotes the preservation and integration of local cultural heritage. By applying legal theory, such as the concept of lex cultura—the legal recognition and protection of cultural rights—this study examines how legal and policy frameworks can ensure the documentation, protection, and integration of local heroes' narratives into educational curricula. Using a multi-method approach over two years, the research maps the values upheld by local heroes in Central Java, and in its second phase, investigates the pedagogical strategies employed by teachers to integrate these values into national education practice. This paper contributes to legal scholarship by discussing the role of law in preserving local knowledge while addressing the challenges and effectiveness of its integration in building national identity among students.